ANALISIS MOTIVASI SISWA DALAM PEMBELAJARAN BAHASA INDONESIA PADA KELAS V SD NEGERI 106836 LIMAU MANIS - Hijjah Safitri Harahap; Samsul Bahri (Yayasan Pendidikan Islam dan Multikultural, 2021)
Indonesian language is the language of unity that becomes the identity of the Indonesian nation, to preserve or develop the Indonesian language can be done by instilling Indonesian language early on. Student motivation in learning Indonesian language is still necessary so that students are able to understand and think and add broad insights. The objective of this research was to describe the motivation of students in Indonesian language learning in grade V students of SD Negeri 106836 Limau Manis. This type of research was qualitative research. This research sample was grade V SD Negeri 106836 Limau Manis. From the results of the data analysis, it was known that student learning motivation was still low because it was seen from the student learning motivation was still low because it was seen from the students’ quastionnnaire.